Application of Reinforcing Thermocycling Treatment for Materials of Stamps Hot Deformation - Berladir K.; Hovorun T.; Bondarenko M.; Shvetsov D.; Vorobiov S. (Журнал інженерних наук)
The paper is devoted to the search for technological methods of increasing the resistance of the stamp tool for hot deformation. New non-standard combinations of cyclization schemes and parameters of thermocycling processing within the regime were developed. This is allowed the creation of managed structural states in the metal due to the grinding of grain, the creation of high density of defects, and the acceleration of diffusion processes to effectively manage the structure, increase the mechanical, operational properties and prevent the destruction of the working surfaces of the tool. New modes of thermocycling treatment, which have a positive effect on the mechanical characteristics of HNM5 steel, have been developed and tested. The conducted heat treatment in experimental modes, consisting of thermocycling treatment as a preliminary, quenching and tempering as the final, allows obtaining a more homogeneous structure with the preservation of fine grain and a given hardness. The grain size of the steel HNM5 structure after the use of thermocycling treatment decreases from 5–6 to 7–8 points, and after the final heat treatment – to 9–10 points.